Preparation and Properties of Agarose-Locust Bean GumHydrated Salt Eutectic Form-Stable Phase Change Materials - Hesman, David S.; Masuoka, Robert E.; Wolfe, Edward J. (Journal of Functional Materials and Applied Engineering, 2022)
A binary eutectic salt mixture comprising Na₂SO₄·10H₂O (SSD) and Na₂HPO₄·12H₂O (SPDD) was initially dispersed in water to mitigate phase segregation within the system. Thereafter, Na₂SiO₃·9H₂O (SMN) was introduced as a nucleating agent to markedly diminish the supercooling degree of the resulting SSD/SPDD/H₂O/SMN composite phase change material. Finally, an agarose-locust bean gum (AG-LBG)/hydrated salt eutectic form-stable phase change material (SSD/SPDD/H₂O/SMN/AG-LBG) was obtained by impregnating the three-dimensional network structure of AG-LBG with SSD/SPDD/H₂O/SMN. The optimal mass ratio of SSD/SPDD salt mixture was determined by DSC analysis, the optimal nucleating agent as well as its addition amount were determined by step cooling test, while the optimal m(AG):m(LBG) and the optimal loading capacity of SSD/SPDD/H₂O/SMN onto the AG-LBG supporting skeleton were determined based on leakage test and simulated working condition experiment. The results showed that the phase transition temperature and enthalpy of the SSD/SPDD mixture prepared with m(SSD):m(SPDD)=52:48 by physical composite were 28.90 °C and 216.40 J/g, respectively. The SSD/SPDD/H₂O/SMN phase change system prepared by water addition amount (based on the mass of SSD/SPDD salt mixture, the same below) of 13% and SMN addition amount of 3% displayed the lowest supercooling degree of 0.16 °C, and of 0.18 °C after 60 cold and hot cycles. The optimal m(AG):m(LBG) ratio of AG-LBG supporting skeleton was 75:25, and the optimal loading capacity of SSD/SPDD/H₂O/SMN phase change system was 85%. The obtained best form-stable phase change material (SSPCM) could maintain 80 min without leakage under the above-mentioned conditions. The SSPCM displayed a melting point of 26.40 °C, an enthalpy of fusion of 147.20 J/g, and a thermal conductivity of 0.11 W/(m·K). Thermal insulation simulations conducted under identical conditions revealed that, in comparison with the foam sandwich reference, the SSPCM-integrated building envelope prolonged the core temperature rise duration by a factor of 2.60 during the heating phase, while the cooling period was extended by 1.37 times.